Relationship between accounting Conservatism, Persistence and volatility of earnings of companies listed on the Iraq Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The study aimed to show the concept and importance of accounting Conservatism, Persistence and volatility of earnings of companies listed in the Iraqi market for securities have been selected 35 companies for the period between 2013 to 2107 used the scale of book value to market value to measure the Conservatism while the current profit regression model was used to measure future profits Eviews 9 was used for the purpose of testing the two hypotheses. The results of the study found that there is a statistically significant relationship between accounting Conservatism and Persistence of earnings. The relationship is inverse with no statistically significant relationship between Conservatism and earnings volatility.